(untitled) (Global Journal of Human-Social Science, 2023)
The article analyzes the implicit aspects of G. Hegel’s doctrine of sublation. It is shown that the negation of negation, the result of which is dialectical sublation, was often treated superficially in the progressivist-revolutionary tradition. It is emphasized that when sublated, it is very important to preserve the content that, at first glance, is negated. Negation is not to be understood as rejection. The doctrine of dialectical sublation is compared with some paradoxical aspects of O. Mandelstam’s worldview, which are most clearly expressed in the poem ’Lamarck’. The question about the truth of simplification, involution, is raised.